2020
DOI: 10.37939/jrmc/vol24.iss1.10
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Perceived benefits of energy drink Consumption in medical students

Abstract: Background: To assess the energy drink consumption patterns and perceived risks and benefits among medical students. The present study was carried out on 332 medical students from Foundation University Medical College. All the students enrolled in foundation university medical college were invited to participate. 332 students, who gave their consent were enrolled in the study. Data was collected by distributing a preformed structured questionnaire among medical students present in their classes. Data was enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In our current study, the prominent reason to consume EDs was to be more alert and awake. Finding from a study among medical students was in harmony with our study, in which the most dominant reasons for ED use were to enhance physical and mental alertness [ 38 ]. Generally, previous studies had found that improving concentration for the study was the most common reason for ED use among adolescents and university students [ 9 , 39 – 41 ].…”
Section: Discussionsupporting
confidence: 82%
“…In our current study, the prominent reason to consume EDs was to be more alert and awake. Finding from a study among medical students was in harmony with our study, in which the most dominant reasons for ED use were to enhance physical and mental alertness [ 38 ]. Generally, previous studies had found that improving concentration for the study was the most common reason for ED use among adolescents and university students [ 9 , 39 – 41 ].…”
Section: Discussionsupporting
confidence: 82%
“…Disturbances in morphodifferentiation may affect the form and size of the tooth without impairing the function of the tooth and the function of ameloblast odontoblasts, thus the result may be a peg shaped/malformed tooth with enamel and dentine that may be normal in structure (Abu-Hussein, Watted and Yehia, 2015). Brook proposed a multifactorial model based on an underlying continuous distribution of tooth size with thresholds determining hypodontia and supernumerary teeth and a general trend that, the more severe, the smaller the size of the tooth formed (Brook et al, 2002;Babar, Amin and Asif, 2020).…”
Section: Introductionmentioning
confidence: 99%